2020
DOI: 10.1007/s40789-020-00366-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coal mining on groundwater of Luohe Formation in Binchang mining area

Abstract: Groundwater of Luohe Formation is the main water source for industrial and agricultural and residential use in Binchang mining area, which is one of the key elements to water conservation coal mining. However, few studies are available to document the enrichment characteristics and influence of underground coal mining on groundwater for the Luohe Formation. This study evaluates the changes of groundwater levels and spring flow caused by mining activities to explore the influence mechanism of coal mining on gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…At the same time, the microcracks continue to develop, the damage increases, the porosity of the rock n increases, and the effective elastic modulus 􏽥 E decreases. e sum caused by elastic deformation can be calculated according to formulas (8) and (11). Here, we will focus on the change Δp 2 in pore water pressure caused by plastic deformation.…”
Section: Pore Water Pressure: B-c "Increase-decrease" Transitional Stagementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the microcracks continue to develop, the damage increases, the porosity of the rock n increases, and the effective elastic modulus 􏽥 E decreases. e sum caused by elastic deformation can be calculated according to formulas (8) and (11). Here, we will focus on the change Δp 2 in pore water pressure caused by plastic deformation.…”
Section: Pore Water Pressure: B-c "Increase-decrease" Transitional Stagementioning
confidence: 99%
“…erefore, the interaction relationship between rock damage propagation and pore water pressure changes can be deeply studied to explore the precursor information of critical fracture pore water pressure of rock mass [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…After the closure of coal mines due to low economic benefit or resource exhaustion, the surface water and groundwater contained in the aquifer rapidly fill underground spaces through the fissured zone, causing a drop in groundwater level, water pollution, surface subsidence, changes in the geological environment, and secondary disasters (Li et al 2019;Sun et al 2021). Within the framework of clean-energy production and ecological restoration of the post-mining areas, considerable efforts have been made worldwide to use geothermal energy, water, and spaces in abandoned coal mines.…”
Section: Introductionmentioning
confidence: 99%
“…Underground coal mining experience has indicated that the LHFA is the main source of water that rushes in from the mine roof and causes disasters in the mining area. 4 Meanwhile, the LHFA has good recharge capability, and it is very difficult to thoroughly drain. In the Binchang mining area, the Gaojiapu coal mine is the deepest one, with a depth reaching 1000 m. At present, four panels, including 12 longwall working (LW) faces, have been developed and they all underlie the highly watery LHFA.…”
Section: Introductionmentioning
confidence: 99%
“…4 coal seam is the Cretaceous Luohe Formation aquifer (LHFA), which is rich in water, as shown in Figure a. Underground coal mining experience has indicated that the LHFA is the main source of water that rushes in from the mine roof and causes disasters in the mining area . Meanwhile, the LHFA has good recharge capability, and it is very difficult to thoroughly drain.…”
Section: Introductionmentioning
confidence: 99%